AS DROPS IN THEIR SEA: ANGELOLOGY THROUGH ONTOLOGY IN FAḪR AL-DĪN AL-RĀZĪ'S AL-MAṬĀLIB AL-῾ĀLIYA. Issue 2 (September 2019) - Hammed, Nora Jacobsen Ben
Abstract: In this article, I examine key passages from the Aš῾arite theologian Faḫr al- Dīn al-Rāzī's (d. 606/1210) final work, Al-Maṭālib al-῾āliya (" The lofty inquiries "), in order to theorize Rāzī's cosmology and angelology. In his attempt to prove the existence of these beings, Rāzī divides reality into material and intelligible realms. Angels, which signify the celestial intellects and spheres, exist as non-space-occupying beings and represent an aspect of the intelligible world. Of these, some are associated with celestial bodies, and others are entirely unassociated with materiality. I then present evidence for the possibility that Rāzī believed that these celestial spiritual beings are pre-eternal with God. These positions indicate a certain degree of conceptual continuity with the falsafa tradition, and reflect al-Ġazālī's (d. 505/1111) previous integration of the philosophical structure of reality into some of his texts. Additionally, one may look to other philosophical currents that developed in the Islamic world beyond the falāsifa, and connect Rāzī's cosmology to both the Hermetic tradition and the Epistles of the Iḫwān al-Ṣafā᾿. Résumé: Dans cet article, j'analyse des passages cruciaux de la composition finale du théologien Faḫr al-Dīn al-Rāzī (d. 606/1210), Al-Maṭālib al-῾āliya (« Les nobles enquêtes »), afin de théoriser sur la nature de deux de ses études : la cosmologie et l'angélologie. En cherchant à prouver l'existence de ces êtres, Rāzī divise la réalité en deux domaines : matériel et intelligible. Les anges, qui symbolisent les intellects et les sphères, existent dans une réalité intelligible comme des êtres qui n'occupent pas d'espace. Parmi eux, certains sont associés aux corps célestes, et d'autres ne s'associent à aucune chose matérielle. Dans un deuxième temps, je présente des arguments suggérant que Rāzī pensait peut-être que ces êtres célestes sont prééternels avec Dieu. Ces conceptions montrent une continuité avec la tradition philosophique islamique, et elles la structure philosophique de la réalité intégrée par al-Ġazālī (d. 505/1111) dans quelques textes théologiques. De plus, on a examiné d'autres courants philosophiques développés dans le monde islamique qui ont pu agir sur la cosmologie de Rāzī, en lien avec la tradition hermétique et avec les Épîtres des frères de la Pureté.